2006
DOI: 10.2466/pr0.99.2.535-546
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Japanese Version of the Positive and Negative Affect Schedule for Children

Abstract: In this paper, the Positive and Negative Affect Schedule for Children originally developed in 1999 by Laurent, et al. was adapted for use in Japan. In Study 1, a total of 763 children in Grades 4 to 6 completed this Schedule, and 103 of them completed it again about three months later. Principal factor analysis with promax rotation identified two factors, positive and negative affect, in the Japanese version, whose alphas (over .80) and test-retest correlations (over .50) were sufficient to indicate internal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Specifically, the EFA revealed that two items, alert and calm, are problematic due to low item-total correlations, whereas CFAs identified additional items, disgusted, fearless, and strong, with low factor loadings. A comparison across translations of the PANAS-C indicated that these results closely correspond to those of previous validation studies (Ciucci et al 2017;Laurent et al 1999;Stevanovic et al 2013;Yamasaki et al 2006). Alert and fearless were eliminated from the original PANAS-C as well as from the Italian, Serbian, and Japanese translations.…”
Section: Itemsupporting
confidence: 80%
See 3 more Smart Citations
“…Specifically, the EFA revealed that two items, alert and calm, are problematic due to low item-total correlations, whereas CFAs identified additional items, disgusted, fearless, and strong, with low factor loadings. A comparison across translations of the PANAS-C indicated that these results closely correspond to those of previous validation studies (Ciucci et al 2017;Laurent et al 1999;Stevanovic et al 2013;Yamasaki et al 2006). Alert and fearless were eliminated from the original PANAS-C as well as from the Italian, Serbian, and Japanese translations.…”
Section: Itemsupporting
confidence: 80%
“…This observation is in line with a general tendency to shorten the PANAS-C by removing poorly performing items. Overall, all translations of the PANAS-C are shorter than their original 27-item counterpart (from the 24-item Japanese and Italian versions [Yamasaki et al 2006;Ciucci et al 2017, respectively] to the 21-item Serbian version [Stevanovic et al 2013]; see also Damásio et al 2013). Our analyses also suggested that some of the PANAS-C items should be eliminated.…”
Section: Itemmentioning
confidence: 66%
See 2 more Smart Citations
“…Two years later, Kiernan et al (2001) administered the PANAS-C to a sample of children ( M age = 11.4, SD = 2.27) from different European countries (Austria, Cyprus, Czech Republic, Denmark, among others) that were attending an international therapeutic prevention program for children with life-threatening illnesses. In Japan, Yamasaki et al (2006) validated the Japanese-language version of the PANAS-C in a sample of children between 9 and 12 years old. Later, Ebesutani et al (2011) confirmed the validity of the PANAS-C in a sample of Hawaiian children and adolescents aged from 8 to 18 years.…”
Section: Introductionmentioning
confidence: 99%